Peningkatan Pemahaman Siswa Kelas IV SD Tentang Wujud Zat Dan Perubahannya Melalui Game Edukasi Ular Tangga - Anissa Putri Ramadhania; Muhammad Suwignyo Prayogo; Ulfatul Rofida Alfikriyah (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
The purpose of this study was to improve the understanding of fourth grade students of SDN Kaliwates 2 Jember about the form of substances and their changes by using snakes and ladders educational game. The background of this research is the lack of interest, motivation, and learning outcomes of students on abstract science materials. The teaching model used integrates the snakes and ladders game with the question mechanics of the lesson, where students who land on a box labeled "boom" are required to answer questions from the material being taught.By integrating the snakes and ladders game with questions about the form of substances and their changes, students can learn actively. By integrating the snakes and ladders game with questions about the form of substances and their changes, students can learn actively. Thus, the snakes and ladders educational game not only serves as a medium of entertainment, but also as an effective learning tool to improve learning outcomes and active engagement of students in the classroom.